2002
DOI: 10.1143/jjap.41.l907
|View full text |Cite
|
Sign up to set email alerts
|

Field Emission from Polycrystalline GaN Grown on Mo Substrate

Abstract: Polycrystalline GaN layers were grown on polycrystalline Mo substrates by gas-source molecular-beam epitaxy using an ionremoval electron-cyclotron-resonance radical cell. The GaN/Mo interface exhibited ohmic characteristics. The atomic force microscopy image for the polycrystalline GaN surface revealed the grain structure with a grain size of 300-600 nm and a tip-like structure around the grains. Field emission measurement was carried out for the polycrystalline GaN/Mo samples. The turn-on electric field was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The as-obtained turn-on elds for different distances are lower than the previously reported values for GaN and other materials, such as CdS, ZnS, and SiC, as compared in Table 1. 9,[26][27][28][29][30][31][32] By comparing the value of the turn-on eld of GaN, as referenced in Table 1, our reported results seem to be quite judicious and reasonable. Based on previous reports and investigations, the lower value of the turn-on electric eld for our GaN lms mainly came from the rough surface.…”
Section: Field Emission (Fe) Properties Characterizationmentioning
confidence: 76%
See 1 more Smart Citation
“…The as-obtained turn-on elds for different distances are lower than the previously reported values for GaN and other materials, such as CdS, ZnS, and SiC, as compared in Table 1. 9,[26][27][28][29][30][31][32] By comparing the value of the turn-on eld of GaN, as referenced in Table 1, our reported results seem to be quite judicious and reasonable. Based on previous reports and investigations, the lower value of the turn-on electric eld for our GaN lms mainly came from the rough surface.…”
Section: Field Emission (Fe) Properties Characterizationmentioning
confidence: 76%
“…To solve this problem, the identication of a commercially available substrate material with a smaller lattice mismatch with GaN has been highly sought aer, such as Mo, Al 2 O 3 , and Si substrate with native oxides. [9][10][11] Recent progress made in the epitaxial growth of GaN lms on MgAl 2 O 4 (111) substrates has reopened the possibility of realizing GaN-based optical devices, overcoming their poor lattice match issues. 12,13 Our previous publications also conrmed that the MgAl 2 O 4 substrate has been shown to be one of the promising nearly lattice-matched substrates for the heteroepitaxial growth of GaN lms of high quality.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that polycrystalline GaN grown on Mo by plasma-assisted molecular beam epitaxy (PA-MBE) exhibits good field-emission characteristics due to a low electron affinity and their grain structures. [12][13][14] When compared with carbon nanotubes (CNTs) [15][16][17][18][19][20] and ZnO-based nanostructures, [21][22][23][24][25][26][27] the field enhancement factor is still low and the resultant turn-on electric field is high. There are two main approaches for realizing good field-emission characteristics, i.e., low onset electric field and high emission current density; one is to lower electron affinity and the other is to enhance the local electric field by using nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Poly-GaN thin-films deposited using reactive rf sputtering were reported as early as in 1972 [26,27] by researchers at IBM corporation. Poly-GaN thin-films have also been explored before for applications such as transparent TFTs [28,29] ("transparent electronics"), LEDs [30] and field electron-emission [31][32][33] as illustrated in Fig. 1.1.…”
Section: Polycrystalline Gan: Materials and Devicesmentioning
confidence: 99%
“…6.3 shows a simulated energy band diagram of the GaN/p-Si heterojunction in which Anderson's model or the electron affinity rule was used [98]. Here, the electron-affinity of GaN was assumed to be 3.3 eV which has been reported before both for crystalline GaN [225,226] and for polycrystalline GaN [31,33]. The large discontinuity in the valence band (∆E v =1.58 eV) as compared to conduction band discontinuity (∆E c =0.7 eV) makes it less likely for holes to participate in the conduction process, at least at lower voltages (< 1.58 V).…”
Section: Electrical Measurementsmentioning
confidence: 99%